TILLAGE, SEED BED CONFIGURATION AND MULCHING: EFFECTS ON SOIL PHYSICAL PROPERTIES, AND RESPONSES OF CASSAVA, COWPEA AND MAIZE - AINA, P. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The influence of tillage, and 2 seed bed configurations on soil physical properties and responses of cassava (Manihot esculenta), cowpea (Vignia unguiculata L. Walp), and maize (Zea mays L.) was studied for two cropping seasons in 1978 under mulch and no-mulch conditions. The study was conducted on an Alfisol at the Ife (Nigeria) University teaching and Research Farm. Tillage reduced soil bulk density at planting (1.43 g/cc) by 23%. Six weeks after seeding, the bulk density of ridges and mounds had increased by 24% compared to 3.5% increase for no-tillage plots under bare condition. Mulching reduced soil compaction of tilled plots by 50% while compaction was negligible on the mulched no-tillage plots. Soil moisture reserve, 3 weeks after planting was higher by 5 and 8 percent (of cumulative rainfall) respectively for no-tillage and ridged plots compared to mounds under unmulched conditions. In the same correspondent order soil temperature was, respectively, lower by 3oC and 1oC than in mounds during the period. Mulch effect on soil moisture and temperature was more significant with no-tillage compared to ridges and mounds. Yield of cassava was reduced by only 13% when grown with no-tillage plus mulch, compared to 40% with no-tillage without mulch. There was no significant effect of tillage on cowpea yield. Yield results reflected differences in soil moisture and temperature regimes which influenced seedling germination, stand and subsequent plant development.